2021
DOI: 10.4103/1735-5362.305192
|View full text |Cite
|
Sign up to set email alerts
|

Protective and therapeutic effects of ethanolic extract of Nasturtium officinale (watercress) and vitamin E against bleomycin-induced pulmonary fibrosis in rats

Abstract: Background and purpose: Pulmonary fibrosis is a chronic disease of the lungs caused by inflammation, species of reactive oxygen, and immune defects. Antioxidant properties of Nasturtium officinale has been reported in some studies. Therefore, the objective of the current study was to evaluate the effect of ethanolic extract of Nasturtium officinale (EENO) on bleomycin (BLM)-induced lung fibrosis in rats. Experimental approach: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
5
13
0
Order By: Relevance
“…In the present study, treatment with the NOE similar to DTX treatment significantly reduced overexpression of the α -SMA gene in OVA-induced asthmatic rats; also the NOE had a noticeable effect on the expression of the inflammatory gene TGF- β . In one study, the antioxidant and anti-inflammatory properties of NOE were suggested to protect against bleomycin-induced pulmonary fibrosis in a rat model [ 65 ]. Accordingly, several studies have reported anti-inflammatory, antioxidant, and immune-regulating effects of the NOE [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, treatment with the NOE similar to DTX treatment significantly reduced overexpression of the α -SMA gene in OVA-induced asthmatic rats; also the NOE had a noticeable effect on the expression of the inflammatory gene TGF- β . In one study, the antioxidant and anti-inflammatory properties of NOE were suggested to protect against bleomycin-induced pulmonary fibrosis in a rat model [ 65 ]. Accordingly, several studies have reported anti-inflammatory, antioxidant, and immune-regulating effects of the NOE [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Group I received a single intratracheal instillation of normal saline (control group) Group II I received a single intratracheal instillation of BLM solution (7.5 IU/kg in 0.9% NaCl) (BLM-treated group) Group III was given a single intratracheal instillation of BLM solution (7.5 IU/kg in 0.9% NaCl) and a daily SPHE (300 mg/kg, gavage) for two weeks (BLM/ PPX 0.5) Group IV received a single intratracheal instillation of BLM solution (7.5 IU/kg in 0.9% NaCl) and a daily SPHE (600 mg/kg, gavage) for two weeks (BLM/PPX 1) Group V was given a single intratracheal instillation of BLM solution (7.5 IU/kg in 0.9% NaCl) and a daily Vit E (500 mg/kg, gavage) for two weeks (BLM/Vit E) e number of animals and the dose of drugs were selected according to previous studies [20,24,25].…”
Section: Methodsmentioning
confidence: 99%
“…Ripe RC fruit was collected in June 2017, from the suburbs of Yasuj, Iran, which was evaluated by Dr. A. Jafari (Botany Department, Natural Resource and Animal Husbandry Research Centre, Yasuj University, Yasuj, Iran) [ 27 ]. The seeds were cleaned, and dust and soil were removed by using distilled water.…”
Section: Methodsmentioning
confidence: 99%